Les modes de perception de la biodiversité par les acteurs et la régulation des usages de l’environnement. Une lecture par les représentations - Muriel Maillefert; Céline Merlin-Brogniart (Développement Durable et Territoires)
This paper questions the relevance of the concept of “services provided by biodiversity”. The discourse of key actors practitioners of biodiversity has been studied.This research investigates the relevance of this notion through the actors’ principles of justification (assumed as plural) as well as its consequences on the biodiversity management. By using French convention theory, different justification polities and worlds of action of actors concerned by biodiversity have been highlighted. The analysis of interviews conducted with actors of the Nord-Pas de Calais Region (firms, associations, and biodiversity managers) in strong link (and sometimes less intense link) with biodiversity shows that the human-nature relationships appears as entering into three categories (Human as dominant, Nature as dominant and integration between Human and Nature).The perception of Nature depends on the scale of analysis, within which Nature is perceived as an object or a system. Given these differentiated perceptions, biodiversity protection policies must be based on appropriate instruments.The notion of Payments for Environmental Services (PES), which often refers to bilateral relationships and market-based instruments appears as limited and inappropriate to stakeholders' expectations at the local level.